Characterization and evaluation of two amorphous silica powders against stored product insect species on concrete surfaces and wheat - Selladurai, Manivannan (Kansas State University, 2024)
Silica based powders are gaining popularity in stored product insect pest management due to their low mammalian toxicity and ease in application. Amorphous silica powders 1 and 2 are two diatomaceous earth formulations provided by Imerys, Lompoc, California, USA. The particle diameter and the shape characteristics of the silica powders 1 and 2 were determined using Morphology G3 instrument. The particle diameter (D₁₀, D₅₀ and D₉₀) of silica powder 1 was significantly smaller than silica powder 2. In terms of shape characteristics, the circularity, convexity, and elongation values of silica powder 1 were significantly higher compared to silica powder 2. The insecticidal efficacy of silica powder 1 and 2 against the red flour beetle, Tribolium castaneum (Herbst); confused flour beetle, Tribolium confusum Jacquelin du Val, saw-toothed grain beetle; Oryzaephilus surinamensis (Linnaeus); rice weevil, Sitophilus oryzae (Linnaeus); and lesser grain borer, Rhyzopertha dominica (Fabricius), was determined by exposing adults to different application rates and exposure times. On concrete surfaces, at application rates of 4.32 to 1.34 g/m², 99% mortality of R. dominica adults was observed when they were exposed to silica powder 1 for 24 to 48 h. In contrast, silica powder 2 at application rates of 0.63 to 0.19 g/m² produced 99% mortality of R. dominica adults when they were exposed for 4 to 12 h. At 15.81 to 5.35 g/m² of silica powder 1, and at 13.31 to 4.65 g/m² of silica powder 2, 99% mortality of S. oryzae adults was observed after exposure for 12 to 48 h. Lower application rates of powders and exposure times were required for both insect species to achieve complete suppression of progeny production, percentage of insect-damaged kernels, and percentage of grain weight loss compared to those required for 99% mortality. Complete mortality of T. castaneum adults was observed when they were exposed to 5 g/m² of silica powder 1after 24 h, whereas a 48 h exposure to ≥ 0.75 g/m² of silica powder 2 was required to achieve complete mortality. Complete mortality of T. confusum adults was achieved at ≥ 4.50 and ≥ 2.50 g/m2 of silica powder 1 and silica powder 2, respectively. At 3.5 g/m² of silica powder 1, complete mortality of O. surinamensis adults was observed after 36 h, while only a 12 h exposure was required when adults were exposed to 4.0 g/m² of silica powder 2. On grains, silica powder 1 applied to wheat at 0.5 g/kg rate produced more than 99% mortality of O. surinamensis and T. castaneum adults. However, ≥ 0.35 g/kg of silica powder 2 on wheat gave more than 99% mortality of O. surinamensis and T. castaneum adults. Complete suppression of O. surinamensis and T. castaneum adult progeny was achieved at ≥ 0.35 g/kg of silica powder 1 and 0.25 g/kg of silica powder 2. Complete mortality, adult progeny suppression of R. dominica, percentage of insect-damaged kernels, and percentage of grain weight loss was achieved only for silica powder 2 at 0.20 g/kg. Silica powder 2 at ≥0.25 g/kg on wheat produced 99% mortality of S. oryzae adults. Complete suppression of S. oryzae progeny production, percentage of insect-damaged kernels, and percentage of grain weight loss was achieved for both powders at 0.30 g/kg. Wheat mixed with 0.35 g/kg of silica powders 1 and 2 resulted in a decrease in bulk density of wheat and an increase in the angle of repose and tapped density. Treating wheat with the 0.35 g/kg of silica powders 1 and 2 caused wheat to change from good flowability to an acceptable flowability, based on the angle of repose, Hausner ratio, and Carr index values. Both silica powders exhibited better insecticidal activity against S. oryzae at lower humidities of 30 ± 2% and 50 ± 5% compared to activity at a humidity of 75 ± 4%. The combination of silica powders with a commercial insecticide powder Gravista-D at 0.09 g/kg containing two active ingredients (deltamethrin and S-methoprene) and an insecticide synergist piperonyl butoxide, resulted in enhanced efficacy in terms of adult mortality, suppression of adult progeny production, inhibition of insect-damaged kernels and grain weight loss, compared to individual application of the powders. Overall, our findings demonstrate that silica powder 2 exhibited greater efficacy compared to silica powder 1 against all insect species on concrete surfaces and wheat, except for T. castaneum on concrete. Both the amorphous silica powders 1 and 2, hold significant promise for safeguarding grains from stored product insect pests in an environmentally friendly manner. Nevertheless, field-oriented studies are warranted to determine the efficacy of these powders applied as grain protectants across various agro-climatic conditions and their effects on grain quality to understand their commercial feasibility for stored product protection.
Keywords: Amorphous silica powders; Stored product insects; Efficacy assessment; Concrete surfaces and wheat; Oil absorption capability; Grain quality